2000
DOI: 10.1103/physrevb.61.11632
|View full text |Cite
|
Sign up to set email alerts
|

Single-ion magnon bound states in an antiferromagnet with strong uniaxial anisotropy

Abstract: Electron-spin-resonance measurements at high frequencies have been made on the antiferromagnet FeI 2 with strong uniaxial anisotropy. We have found signals whose g value is 16.5 together with the one with gϭ7.0 reported before ͓A. R. Fert et al., Solid State Commun. 26, 693 ͑1978͔͒. We interpret these electron-spin resonance signals as originating from single-ion four magnon and two magnon bound states, respectively. The energies for creating the magnon bound states are calculated using an Ising approximation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The same approach can also be applied to quasi-two-dimensional frustrated magnets [49]. So far multi-magnon bound states have been observed mostly in quasi-one-dimensional compounds but with different experimental techniques, such as absorption spectroscopy [6-12, 15, 17], inelastic neutron scattering [18,21] and electron spin resonance [13,14,16,19,20,22,23]. The same spectroscopic measurements can be used here to observe the emergent Efimov states of magnons, provided that the conservation of the magnetization along the magnetic field axis is weakly violated [8,9,20].…”
Section: Towards Experimental Realizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The same approach can also be applied to quasi-two-dimensional frustrated magnets [49]. So far multi-magnon bound states have been observed mostly in quasi-one-dimensional compounds but with different experimental techniques, such as absorption spectroscopy [6-12, 15, 17], inelastic neutron scattering [18,21] and electron spin resonance [13,14,16,19,20,22,23]. The same spectroscopic measurements can be used here to observe the emergent Efimov states of magnons, provided that the conservation of the magnetization along the magnetic field axis is weakly violated [8,9,20].…”
Section: Towards Experimental Realizationmentioning
confidence: 99%
“…We will also propose several approaches to experimentally realize the Efimov effect in quantum magnets, including frustrated cases. So far multi-magnon bound states have been observed with different experimental techniques, but mostly in quasi-one-dimensional compounds [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Although the Efimov effect emerges only in three dimensions [3,4], the same spectroscopic measurements can be used to observe the emergent Efimov states of magnons.…”
Section: Introductionmentioning
confidence: 99%
“…The steep field-slope of several branches is clear evidence for their multi-magnon character, as discussed further below. Earlier far-infrared spectroscopy and electron spin resonance studies [22,23] observed the zero-field absorption branches at ν = 0.65, 0.88 and 0.97 THz. The high energy and field resolution of our experiments uncover new and very steep branches, as well as additional details that are important to fully understand the lowenergy excitations of FeI 2 (see Supplemental Information for comparison to earlier results).…”
Section: Methodsmentioning
confidence: 89%
“…∈ N is the particle number. Such measurements were performed on FeI 2 by means of infrared absorption [153,154], neutron scattering [155], and electron spin resonance [156]. However, with coupling, spin sectors mix and ∆S n (k) can assume any value, as recently seen in FeI 2 by terahertz spectroscopy [51].…”
Section: Spectroscopymentioning
confidence: 99%